Uric acid versus non-uric acid renal stones: in vivo differentiation with spectral CT. Issue 6 (June 2017) - Lombardo, F.; Bonatti, M.; Zamboni, G.A.; Avesani, G.; Oberhofer, N.; Bonelli, M.; Pycha, A.; Pozzi Mucelli, R.; Bonatti, G.
Abstract : Aim: To differentiate uric acid from non-uric acid renal stones based on their spectral attenuation values. Materials and methods: The present study was approved by the institutional review board and the need for informed consent was waived. Thirty-three consecutive patients (21 men, 12 women; mean age 55 years) with symptomatic urolithiasis underwent dual-energy computed tomography (DECT) using a second-generation dual-source CT system. Stone composition was assessed by means of chemical analysis after extraction or spontaneous expulsion. The composition of one stone was considered to represent all remaining stones in patients presenting with more than one stone. Image-domain virtual monoenergetic images were generated from the dual-energy datasets. One radiologist evaluated stone attenuation values from 40 to 190 keV; attenuation curves were created and 40/190 keV attenuation ratios calculated. Qualitative evaluation of the spectral attenuation curves was also performed. Imaging findings were compared with laboratory results. Results: Sixty-two stones were considered in 33 patients (mean diameter 6.5 mm). Fifteen of the 62 stones were mainly composed of uric acid and 47/62 of cysteine or calcium oxalates/phosphates. Forty to 190 keV attenuation ratios were significantly lower for uric acid stones (mean 0.87±0.3) than for non-uric acid stones (mean 3.80±0.6; p <0.0001). Accuracy was 100% with a cut-off value of 1.76. Qualitative analysis of spectral attenuation curves showed unique shapes for uric acid and non-uric acid stones. Conclusions: Spectral CT quantitatively and qualitatively differentiates uric acid from non-uric acid stones. Highlights: 40/190 keV attenuation ratios are significantly lower for uric acid stones than for non-uric acid stones (p<0.0001). A cut-off value of 1.760 has 100% sensitivity and specificity in differentiating between uric acid and non-uric acid stones. Spectral attenuation curves show different shapes between uric acid and non-uric acid stones.